Knowledge and practice regarding preventive measures of dengue fever among community people of Jhapa district. - Pakuwal,Sandhya (2018)
ABSTRACT: In Nepal, Terai region is high risk for dengue fever. Highly affected districts are Chitwan, Jhapa, Rupandehi and other districts of Terai region. The descriptive crosssectional study was conducted to assess Knowledge and Practice regarding preventive measures of dengue fever among community people of Birtamod-2, Jhapa District. Non-probability purposive sampling technique was used to select the sample. Structured interview questionnaire was used to collect data regarding level of knowledge and preventive practices. Obtained data were analyzed using descriptive statistics such as frequency, mean, percentage and standard deviation and inferential statistics such as Chi-square test, Fisher exact test & Pearson's Co-relation using SPSS version 20. Findings of the study revealed that only 15.8% of the respondents had good level of knowledge regarding dengue fever. Despite of poor level of knowledge, most of the respondents (89.2%) had good level of practice regarding preventive measures of dengue fever. There was significance association between ethnicity (p=0.022) and knowledge level regarding dengue fever and also significant association was found between age (p-value=0.034) and practice level regarding preventive measures of dengue fever. Sources of information like books (p-value=0.030), parents (pvalue=0.006) and health personnel (p-value=0.000) were associated with knowledge level regarding dengue fever. . On the basis of findings of the study, it can be concluded that though the preventive practices regarding dengue fever is good, the level of knowledge is poor among them. So, it is necessary to conduct public awareness program by the local level government. Keywords: Community people, Dengue fever, knowledge, Practice